Conflict Management Vs. Conflict Resolution In The Nagorno-Karabakh Peace Process: Understanding The Azerbaijani Approach - Aghajanyan, Elya (ՀՀ ԳԱԱ Արևելագիտության ինստիտուտ)
The aim of this paper is to explore the dynamics of Azerbaijan’s policy towards Armenia in the framework of the NK peace process with a particular emphasis on the concept of ‘strategic patience.’ The theoretical part of the paper discusses two key terms of peace studies: conflict management and conflict resolution. Also covered are the determinants which shape and distinguish between these two terms and their strategies, putting “strategic patience” within the broader framework of conflict management strategies. Then the manifestations of Azerbaijani policies towards the peace process since its independence to 2019 are analyzed. Primarily, this article discusses the conflict resolution efforts made by the mediators and, in that context, the various means and approaches that Azerbaijan has utilized in between these processes. It analyses the speeches of Azerbaijani leaders in order to understand their position.
Keywords: International relations